The Importance of Livelihood Diversification on Agroforestry Farmers in The Landslide Prone Area: A Case Study in Menoreh Hills Kulon Progo, Indonesia - Mutiarra Ridyo Arum; Arini Wahyu Utami; Irham Irham (BIO Web of Conferences, 2023)
Menoreh Hill in Kulon Progo is one of the most prone and vulnerable areas to natural disasters due to its location in an old volcanic complex, which can severely affect the livelihoods of agroforestry farmers. Diversification has become a livelihood improvement strategy in the landslide-prone area. This study specifically examines how and to what extent farmers diversify their livelihoods by comparing agroforestry farmers in high-risk areas (Samigaluh) and low-risk areas (Kalibawang). Primary data were collected from 54 farm households in Samigaluh and 51 farm households in Kalibawang districts using the census technique. The livelihood diversification index was calculated using the Simpson Diversification Index (SDI) and used an independent sample t-test to test whether groups of farmers would differ regarding livelihood diversification. The results showed that farmers in Samigaluh have a relatively higher diversification index (0.3994) than farmers in Kalibawang (0.3864). The results also show that diversification doesn’t always bring higher income to farming households, but it is essential to survive in the landslide-prone area.